Developing Heritage - Developing Countries Ethiopian Nation-Building and the Origins of UNESCO World Heritage, 1960-1980 - Huber, Marie (Africa in Global History, 2020)
Seven Ethiopian heritage sites were among the first sites on the UNESCO World Heritage List - a stunning number for an African country at the time and the product of extended international technical assistance and tourism planning. This book unpacks the beginnings of World Heritage in development thinking and the significance of national heritage for developing countries in a global context during the 1960s and 1970s.